Late Holocene environmental changes and anthropogenic impact in Dee Why Lagoon, New South Wales. Issue 5 (4th July 2019) - Chagué, C.; Edwards, D.; Ruszczyk, J.; Gadd, P.; Zawadzki, A.; Jacobsen, G.; Fierro, D.; Goralewski, J.; Clement, L.; Albani, A.
Abstract: Late Holocene environmental changes were examined in Dee Why Lagoon, New South Wales, based on the sedimentological, geochemical and geochronological analysis of six cores collected from the fluvial delta and lagoon basin. The lagoon formed about 7300–7200 cal yr BP, following the post-glacial marine transgression and establishment of a sand barrier. Infilling of the lagoon occurred at a rate of 0.09–0.15 mm/yr until about 3300–3200 cal yr BP, when the barrier closed, resulting in mostly freshwater conditions, as evidenced by a change from pyrite-rich units to sediment containing little sulfur and a lack of foraminifera. Sedimentation rates increased to 0.23 then 0.43 mm/yr until about 100 years ago. Post-European land clearance led to an increase in sedimentation rates to 1.0–1.3 mm/yr on the fluvial delta, which are lower than those from other wave-dominated estuaries in New South Wales as well as those estimated by previous studies in Dee Why Lagoon. Our study shows that the fluvial delta started forming much earlier than originally thought, based on results of radiometric dating, and confirmed using sedimentological and geochemical data, as well as a critical examination of historic aerial photographs. Human impact has resulted in an increase in heavy metal (Cu, Pb, Zn) and metalloid (As) concentrations in the recent sediment, most likely attributed to stormwater discharge. Pb and As concentrations are above the ANZECC high sediment quality guideline values at the site closest to the stormwater outlet, with As-based pesticides one of the possible sources. Using the mean enrichment quotient, which is based on normalised Cu, Pb and Zn concentrations over their normalised background concentrations, we show that the surface sediments in Dee Why Lagoon are severely enriched, reflecting the recent anthropogenic impact that has also led to an increase in sedimentation rates.